Divulgação científica por meio de ferramentas digitais : estudo de caso do portal do Instituto de Física de São Carlos (IFSC/USP) - Spina, Tatiana Gladcheff Zanon (2016)
Quali-quantitative diagnosis of São Carlos Institute of Physics (IFSC/USP) website to verify its communicational effectiveness with intern (IFSC/USP teachers, employees and students) and extern public. The quantitative analysis, that considered 2.441 news, posted between June 2011 and December 2015, it was based on data provided by Google Analytics tool, considering three main topics: geographic and demographic users profile, views and time remaining on each one of the pages. The qualitative analysis considered topics related to website´s content, usability and functionality. It was concluded that news related to Everyday Physics, Health and Medicine and Opportunities were responsible for the biggest accesses and time of permanence of the users on the website. The study proposes the insertion of more interactive tools e multimedia resources on the website to attract more extern users as well as to bring more visibility to the website and the institution.